THERMAL MODELS AND CLAY DIAGENESIS IN THE TERTIARY-CRETACEOUS SEDIMENTS OF THE ALAVA BLOCK (BASQUE-CANTABRIAN BASIN, SPAIN) - Arostegui J.; Sangüesa F.J.; Nieto F.; Uriarte J.A. (My University, 2006)
Diagenesis in the Cretaceous and Tertiary sediments of the Alava Block (Basque-Cantabrian basin) has been studied using the clay mineralogy (X-ray diffraction) of cuttings from three representative wells of a N-S cross-section. More than 5500 m of various lithologies (marls, mudstones and sandstones) have been drilled in the northern part of the domain, and 2100 m in the southern zone. The illitization of smectite and the disappearance of kaolinite, due to diagenesis, are the most characteristic features in the northern well. Evolution of smectite to illite has been differentiated into four zones, from top to bottom of the series, each showing specific I-S interstratified clay assemblages. The disappearance of smectite and the distribution of kaolinite in the other two wells are explained based on source-area considerations. Burial and thermal history have been reconstructed, revealing a northward increase in thermal flow until the Oligocene (Alpine orogeny paroxysm). In the northern well, the thermal model suggests temperatures of 160 and 270°C for the disappearance of smectite (R0) and illite-smectite (I-S) mixed-layer R1 clay minerals, respectively. The disappearance of kaolinite is related to a temperature of 230°C, a temperature never attained in the other two wells. Retardation of these processes, in relation to temperature values in the literature, is a consequence of the poor reactivity of marly lithologies, due to the low availability of cations. In this regard, the scarcity of reactants (K-bearing phases) and the absence of pathways (low permeability) for their access and circulation imply that illitization could have taken place in a closed system, by diffusion, on a very small scale, i.e. that of the original smectite grains.
Keywords: BASQUE-CANTABRIAN BASIN; DIAGENESIS; ILLITE-SMECTITE; ILLITIZATION; MARLS; RETARDATION; TEMPERATURE; THERMAL MODELLING; WELLS; Cretaceous; Oligocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен